Margin constraints and asset prices - Ahn, Jungkyu (Review of Finance, 2025)
Abstract I study the effects of regulatory policy changes on interest rate option prices: margin tightening from the introduction of mandatory interest rate swap clearing by the Dodd–Frank Act in 2010 and margin loosening from the counterbalance of voluntary swaption clearing and synthetic derivatives to the uncleared margin rule in 2016. Employing these variations as exogenous shocks for a quasi-experimental design, I show that swaption prices consistently respond to changes in margin requirements. The results are consistent with theories on the expected margin premium, where the constrained agent holds short positions in zero net supply.